C. Christopher Soufas, Conflict of light and wind. The Spanish generation of 1927 and the ideology of poetic form. Wesleyan University Press, Middletown, CT, 1989; 279 pp. - Valender, James (El Colegio de México, 1991)
Se reseñó el libro: Conflict of light and wind. The Spanish Generation of 1927 and the ideology of poetic form.